Prioritas Lingkungan dalam Model Bisnis Alternatif: Pendekatan Hukum dan Doughnut Economy - Modeong, Indriati; Sunarno; Mukti Fajar ND (Media Iuris, 2024)
The Donut Economy visualization emphasizes how important it is to balance social and ecological boundaries to ensure a safe and equitable space for everyone. This research aims to determine the benefits of the Donut Economy concept in prioritizing environmental health in alternative business models by reforming laws in Indonesia. This normative legal research uses a comparative approach. Comparisons were made between Indonesia and the Netherlands. The results of this research found that the Netherlands has succeeded in applying the Donut Economy concept to reorganize cities after the Covid-2019 pandemic, such as the City of Amsterdam. Although Indonesia has legislation on environmental priorities such as the Government Regulations Replacing the Law (Perpu) No. 2 of 2022 on the Creation of Work Section 22, the existing regulations are still not strong enough to emphasize the priorities of the environment for business operators in Indonesia. From that, it is expected that Indonesia will follow the strategy taken by the Netherlands in implementing the concept of the doughnut economy, which should focus on the creation of a circular economy and participate in initiatives such as sharing platforms, used goods stores, online markets, and repair services.